Maintenance of Stem Cell Niche Integrity by a Novel Activator of Integrin Signaling. - Joo Yeun Lee; Jessica Y Chen; Jillian L Shaw; Karen T Chang (PLoS Genetics)
Stem cells depend critically on the surrounding microenvironment, or niche, for their maintenance and self-renewal. While much is known about how the niche regulates stem cell self-renewal and differentiation, mechanisms for how the niche is maintained over time are not well understood. At the apical tip of the Drosophila testes, germline stem cells (GSCs) and somatic stem cells share a common niche formed by hub cells. Here we demonstrate that a novel protein named Shriveled (Shv) is necessary for the maintenance of hub/niche integrity. Depletion of Shv protein results in age-dependent deterioration of the hub structure and loss of GSCs, whereas upregulation of Shv preserves the niche during aging. We find Shv is a secreted protein that modulates DE-cadherin levels through extracellular activation of integrin signaling. Our work identifies Shv as a novel activator of integrin signaling and suggests a new integration model in which crosstalk between integrin and DE-cadherin in niche cells promote their own preservation by maintaining the niche architecture.